PHYTOCHEMICAL ANALYSIS OF CITRUS KARNA FRUIT - R. GHONGADE (International Journal of Pharma and Bio Sciences, 2013)
Citrus fruits have long been valued as part of a nutritious and tasty diet. The flavors provided by citrus are among the most preferred in the world, and it is increasingly evident that citrus not only tastes good, but is also good for Health. The present study focuses on the phytochemical analysis of fruit of Citrus karna. The phytochemical screening of both ethanolic and aqueous fruit extracts revealed the presence of various secondary metabolites such as carbohydrates, alkaloids, Phytosterols, phenolic compounds, tannins, flavonoids, Cumarine, amino acids, terpenoids and saponins. Also in present work, total chlorophyll content of fruit peel is calculates which shows strong chlorophyll content in Ethanolic extract of peel. The FTIR analysis of the crude extract of peel gives information about the distribution of functional groups and provides a basis for comparison of compositional differences between isolates and among samples.